Mesenchymal Stem Cell Fate: Applying Biomaterials for Control of Stem Cell Behavior - Anderson, Hilary J.; Sahoo, Jugal Kishore; Ulijn, Rein V.; Dalby, Matthew J. (Frontiers in Bioengineering and Biotechnology, 2016)
Mesenchymal Stem Cell Fate: Applying Biomaterials for Control of Stem Cell Behaviour Hilary J Anderson1, Jugal Kishore Sahoo2, Rein V Ulijn2,3, Matthew J Dalby1* 1 Centre for Cell Engineering, University of Glasgow, Glasgow, UK. 2 Technology and Innovation centre, Department of Pure and Applied Chemistry, University of Strathclyde, Glasgow, UK. 3 Advanced Science Research Centre (ASRC) and Hunter College, City University of New York, NY 10031, NY, USA. Correspondence: *Hilary Anderson h.anderson.1@research.gla.ac.uk Keywords: mesenchymal stem cells, bioengineering, materials synthesis, nanotopography, stimuli responsive material□ Abstract The materials pipeline for biomaterials and tissue engineering applications is under continuous development. Specifically, there is great interest in the use of designed materials in the stem cell arena as materials can be used to manipulate the cells providing control of behaviour. This is important as the ability to ‘engineer’ complexity and subsequent in vitro growth of tissues and organs is a key objective for tissue engineers. This review will describe the nature of the materials strategies, both static and dynamic, and their influence specifically on mesenchymal stem cell fate.